2012
DOI: 10.1089/jwh.2011.3376
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Adherence to Chlamydia Screening Guidelines Among Title X Providers and Non-Title X Providers in the California Family Planning, Access, Care, and Treatment Program

Abstract: Background: Annual chlamydia screening is recommended for adolescent and young adult females and targeted screening is recommended for women ‡ 26 years based on risk. Although screening levels have increased over time, adherence to these guidelines varies, with high levels of adherence among Title X family planning providers. However, previous studies of provider variation in screening rates have not adjusted for differences in clinic and client population characteristics. Methods: Administrative claims from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Previous literature identifies ambivalence toward pregnancy (Murray et al., 2013; Sales et al., 2012), perception of fidelity (Bonacquisti & Geller, 2013; Sales et al., 2012), and partner’s negative attitude toward condoms (Daniels et al., 2013; Mosher et al., 2012; Sales et al., 2012) as antecedents of condom nonuse. In addition, high homicide and incarceration rates of Black men (Chesson et al., 2012; Swartzendruber et al., 2012), high rates of concurrent relationships (Waldrop-Valverde et al., 2013), and high rates of screening among low-income women (Chow et al., 2012) have been noted as determinants of negative sexual health outcomes among Black women. More recent events such as the current opioid epidemic may be associated with increasing STD rates, as illicit drug users have more than twice the risk of contracting an STD as compared to those who do not use drugs (Acheampong et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature identifies ambivalence toward pregnancy (Murray et al., 2013; Sales et al., 2012), perception of fidelity (Bonacquisti & Geller, 2013; Sales et al., 2012), and partner’s negative attitude toward condoms (Daniels et al., 2013; Mosher et al., 2012; Sales et al., 2012) as antecedents of condom nonuse. In addition, high homicide and incarceration rates of Black men (Chesson et al., 2012; Swartzendruber et al., 2012), high rates of concurrent relationships (Waldrop-Valverde et al., 2013), and high rates of screening among low-income women (Chow et al., 2012) have been noted as determinants of negative sexual health outcomes among Black women. More recent events such as the current opioid epidemic may be associated with increasing STD rates, as illicit drug users have more than twice the risk of contracting an STD as compared to those who do not use drugs (Acheampong et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of chlamydia screening in the Family PACT program found that providers did not consistently adhere to age-specific guidelines that required annual testing of women under 25 years and only risk-specific screening of women 25 years and over. 30,,31 Medical record systems that provide reminders of upcoming screening tests to clinicians or patients could facilitate adherence to triennial screening guidelines. This study of Family PACT providers included a diverse group of public clinics and private group offices with widely varying practice management systems that show the challenges of successfully implementing new clinical guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found Region X Title X clinic screening coverage ranged from 11–92%. 22 Additionally, Chow et al 16 found that screening coverage among women aged 25 years or younger was higher among Title X providers than non–Title X public and private providers in California.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Screening coverage varies by health plan (commercial vs Medicaid plans), as well as by provider characteristics including Title X participation, patient volume, public versus private sites, patient volume, percent urban/rural location, and percent African American patients. 3,16 Exploring variation in screening at multiple levels (ie, across states and amongst patients) may uncover missed opportunities for testing and inform future interventions to improve screening coverage.…”
mentioning
confidence: 99%